2018
DOI: 10.18332/ejm/95283
|View full text |Cite
|
Sign up to set email alerts
|

A survey among women who continued smoking during pregnancy in Slovenia

Abstract: INTRODUCTIONSmoking in pregnancy is unhealthy and can also have negative effects on the foetus. However, there are still some women who do not quit smoking during pregnancy. The aim of the study was to identify Slovenian women at risk who smoke during pregnancy. METHODS A quantative approach using an online survey was adopted. RESULTS More than half (66%) did not quit smoking during pregnancy. Women who continued to smoke during pregnancy were usually younger, less educated with a partner who smoked. Women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In China, approximately 3.8% of women smoked [29]. More than 7 million deaths are the result of direct tobacco use, while about 1.2 million are the result of exposure of non-smokers to tobacco smoke (passive smoking) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, approximately 3.8% of women smoked [29]. More than 7 million deaths are the result of direct tobacco use, while about 1.2 million are the result of exposure of non-smokers to tobacco smoke (passive smoking) [10].…”
Section: Introductionmentioning
confidence: 99%
“…More studies have identified many factors associated with smoking during pregnancy, including maternal age, educational level, low socioeconomic status, exposure to secondhand smoke and various environments, age of onset of smoking, increasing the level of smoking dependence, and increasing the level of stress [15]. Smoking for women and girls often involves cultural, psychosocial, and socioeconomic factors, including body image and societal impact [23].Women who smoke during pregnancy have friends and family members who are smokers [22] and less knowledge of the side effects of pregnancy smoking and had low intentions to quit smoking compared to women who had high intentions to quit smoking. The partners, family members, and colleagues, of pregnant women, can influence women who smoke during pregnancy in behavior toward smoking.…”
Section: Introductionmentioning
confidence: 99%